Hybrid Organometallic and Enzymatic Tandem Catalysis for Oxyfunctionalisation Reactions. Issue 7 (24th March 2023) - Domestici, Chiara; Wu, Yinqi; Hilberath, Thomas; Alcalde, Miguel; Hollmann, Frank; Macchioni, Alceo
Abstract: Unspecific peroxygenases (UPOs) are promising biocatalysts for oxyfunctionalisation reactions, owing to their simplicity of handling, stability and robustness. A limitation of using UPOs on a large scale is their deactivation in the presence of even rather modest concentrations of H2 O2, requiring a constant and controlled supply of low amount of H2 O2 . Herein, we report an organometallic complex [Cp*Ir(pica)NO3 ] {pica=picolinamidate=κ 2 ‐pyridine‐2‐carboxamide ion (−1)} 1 capable of efficiently regenerating FMNH2 from FMN (TOF=350 h −1, 298 K), driven by NaHCOO; FMNH2, in turn, spontaneously reacts with O2 leading to H2 O2 . After having studied the compatibility of 1 with the UPO from Agrocybe aegerita (r Aae UPO PaDa‐I) and individuated the best experimental conditions, we applied such a hybrid catalytic tandem in some hydroxylation, epoxidation and sulfoxidation reactions. Best performances were obtained by using a 1 /r Aae UPO molar ratio of 50. TONs for the biocatalyst of up to 18933 were obtained for the transformation of ethylbenzene derivatives into ( R )‐1‐phenylethanols (ee>99 %). 1 /r Aae UPO was found to oxidise also cis ‐methyl styrene (TON=13488), leading exclusively (1 R, 2 S )‐ cis ‐methyl styrene oxide (ee>99 %), cyclohexane (TON=1634) and thioanisole (TON=1369). Abstract : Let′s help each other : This study shows how [Cp*Ir(pica)NO3 ], which generates H2 O2 by NaHCOO and O2, assisted by FMN co‐catalyst, can successfully cooperate with r Aae UPO, which takes advantage by the in situ produced H2 O2 to efficiently oxyfunctionalise a rather wide range of aromatic and cyclo aliphatic substrates.